A structural and biological study on the new 3, 5-diacetyl-1, 2, 4-triazol bis(p-chlorophenylthiosemicarbazone) ligand and its bimetallic complexes. Issue 1 (5th December 2014) - Matesanz, A. I.; Albacete, P.; Perles, J.; Souza, P.
Abstract : Preparation and characterization of the new ligand 3, 5-diacetyl-1, 2, 4-triazol bis( 4 N-p -chlorophenylthiosemicarbazone), H5 L 1, and its bimetallic complexes [Pd(μ-H3 L 1 )]2 and [Pt(μ-H3 L 1 )]2, are described. Abstract : Preparation and characterization of the new ligand 3, 5-diacetyl-1, 2, 4-triazol bis( 4 N-p -chlorophenylthiosemicarbazone), H5 L 1, and its bimetallic complexes [Pd(μ-H3 L 1 )]2 and [Pt(μ-H3 L 1 )]2, are described. The molecular structure of the complexes, determined by single crystal X-ray crystallography, reveals that each ligand coordinates, in an asymmetric dideprotonated form, to the metal ions in a square planar geometry. The new compounds synthesized have been evaluated for antiproliferative activity in vitro against NCI-H460, T-47D, A2780 and A2780cisR human cancer cell lines. The cytotoxicity data suggest that these compounds may be endowed with important antitumor properties, especially H5 L 1, since they exhibit excellent antiproliferative activity surpassing the activity of cisplatin against three of the four tumor cell lines studied. The DNA binding ability of H5 L 1 and [Pt(μ-H3 L 1 )]2 with calf thymus DNA in Tris-HCl buffer solution (pH = 7.2) was explored by UV-Vis absorption spectroscopy and viscosity measurements. These data indicated that both compounds bind to DNA by a groove binding mode.